The role of trained immunity in sepsis - Wang, Wenjuan; Ma, Lisi; Liu, Bin; Ouyang, Liangliang (Frontiers in Immunology, 2024)
Sepsis is defined as a life-threatening organ dysfunction syndrome caused by dysregulated host response to infection, characterized by a systemic inflammatory response to infection. The use of antibiotics, fluid resuscitation, and organ support therapy has limited prognostic benefit in patients with sepsis, and its incidence is not diminishing, which is attracting increased attention in medicine. Sepsis remains one of the most debilitating and expensive illnesses. One of the main reasons of septic mortality is now understood to be disruption of immune homeostasis.Immunotherapy is revolutionizing the treatment of illnesses in which dysregulated immune responses play a significant role. This "trained immunity", which is a potent defense against infection regardless of the type of bacteria, fungus, or virus, is attributed to the discovery that the innate immune cells possess immune memory via metabolic and epigenetic reprogramming. Here we reviewed the immunotherapy of innate immune cells in sepsis, the features of trained immunity, and the relationship between trained immunity and sepsis.